2021
DOI: 10.1371/journal.pgen.1009862
|View full text |Cite
|
Sign up to set email alerts
|

Porcine ZBED6 regulates growth of skeletal muscle and internal organs via multiple targets

Abstract: ZBED6 (zinc finger BED domain containing protein 6) is a transcription factor unique to placental mammals and its interaction with the IGF2 (insulin-like growth factor 2) locus plays a prominent role in the regulation of postnatal skeletal muscle growth. Here, we generated lean Bama miniature pigs by generating ZBED6-knockout (ZBED6−/−) and investigated the mechanism underlying ZBED6 in growth of muscle and internal organs of placental mammals. ZBED6−/− pigs show markedly higher lean mass, lean mass rate, larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…After ZBED6 knockout, the IGV of RNA-seq results showed that IGF2 was significantly upregulated in myocardial tissue. Previous studies have confirmed with RT–qPCR that IGF2 expression is significantly higher in ZBED6 -KO group than in the ZBED6 -WT group [ 26 ], which is consistent with the results in mice and cattle [ 4 , 6 , 7 ]. We again confirmed the reliability of our data.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…After ZBED6 knockout, the IGV of RNA-seq results showed that IGF2 was significantly upregulated in myocardial tissue. Previous studies have confirmed with RT–qPCR that IGF2 expression is significantly higher in ZBED6 -KO group than in the ZBED6 -WT group [ 26 ], which is consistent with the results in mice and cattle [ 4 , 6 , 7 ]. We again confirmed the reliability of our data.…”
Section: Discussionsupporting
confidence: 89%
“…Previous histological analysis of myocardial HE-stained sections showed that knockout of ZBED6 resulted in thicker myocardial muscle fibers and a reduction in connective tissue. These findings are complementary to the heart weight results, indicating that ZBED6 knockout could promote the growth and development of pig hearts to a certain extent [ 26 ].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The G-to-A mutation or ZBED6-binding site deletion of IGF2 disrupts the binding of the transcriptional repressor ZBED6, thereby increasing the expression of IGF2 [ 12 , 13 ]. Both Zbed6 -knockout mice and ZBED6-binding-site-mutant mice showed enlargement of muscles and internal organs, similar to the findings in pigs with corresponding mutations [ 14 , 15 ]. Furthermore, the muscle enlargement in mice was significantly greater than that in pigs (15–20% vs. 3–4%, respectively), probably because of the long-term selection of pigs for muscle growth [ 15 ].…”
Section: Introductionsupporting
confidence: 80%